OPTIMALISASI PROGRAM SUPERVISI AKADEMIK BERBASIS COACHING DALAM MENINGKATKAN KUALITAS PEMBELAJARAN DI SD NEGERI 229 CIBADUYUT KOTA BANDUNG TAHUN PELAJARAN 2025-2026 - Lilis Suwandari; Ai Yunita; Romlah Rosmawati; Neneng Dian Handayani; Kiki Yuwantika; Jejen Rohandi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to optimize a coaching-based academic supervision program using the TIRTA (Objective, Identification, Action Plan, and Responsibility) model to improve the quality of learning at SD Negeri 229 Cibaduyut, Bandung, in the 2025-2026 academic year. Using a School Action Research (PTS) design with a predominantly qualitative approach, the study involved 16 teachers as subjects. The supervision process was integrated into three stages: pre-observation, observation, and post-observation, with TIRTA coaching implemented in two main action cycles, preceded by a pre-cycle as a baseline. Data were collected through classroom observations, interviews, and checklists, and analyzed descriptively using score categorization. The results showed a significant improvement: the average supervision score from the pre-cycle (70, good category) increased to 81.5 in cycle I and 86.78 in cycle II (very good category), representing an overall 23.97% increase. Improvements were seen in administrative and classroom aspects, supported by collaboration, intense communication, and a humanistic approach aligned with national policies such as Permendikbud No. 16/2022, Perdirjen GTK No. 2626/2023, and the Independent Curriculum. The conclusion states that TIRTA coaching-based supervision effectively improves teachers' pedagogical competence, contributing to the quality of continuing education. Recommendations: consistent monitoring and further research to address challenges such as time constraints.